Loss of function of BRCA1 promotes EMT in mammary tumors through activation of TGFβR2 signaling pathway - Bai, Feng; Wang, Chuying; Liu, Xiong; Hollern, Daniel; Liu, Shiqin; Fan, Cheng; Liu, Chang; Ren, Sijia; Herschkowitz, Jason I.; Zhu, Wei-Guo; Pei, Xin-Hai (Cell death & disease, 2022)
BRCA1 deficient breast cancers are aggressive and chemoresistant due, in part, to their enrichment of cancer stem cells that can be generated from carcinoma cells by an epithelial-mesenchymal transition (EMT). We previously discovered that BRCA1 deficiency activates EMT in mammary tumorigenesis. How BRCA1 controls EMT and how to effectively target BRCA1-deficient cancers remain elusive. We analyzed murine and human tumors and identified a role for Tgfβr2 in governing the molecular aspects of EMT that occur with Brca1 loss. We utilized CRISPR to delete Tgfβr2 and specific inhibitors to block Tgfβr2 activity and followed up with the molecular analysis of assays for tumor growth and metastasis. We discovered that heterozygous germline deletion, or epithelia-specific deletion of Brca1 in mice, activates Tgfβr2 signaling pathways in mammary tumors. BRCA1 depletion promotes TGFβ-mediated EMT activation in cancer cells. BRCA1 binds to the TGFβR2 locus to repress its transcription. Targeted deletion or pharmaceutical inhibition of Tgfβr2 in Brca1-deficient tumor cells reduces EMT and suppresses tumorigenesis and metastasis. BRCA1 and TGFβR2 expression levels are inversely related in human breast cancers. This study reveals for the first time that a targetable TGFβR signaling pathway is directly activated by BRCA1-deficiency in the induction of EMT in breast cancer progression.